Isolation and molecular identification of a siderophore producing bacterium and its antagonistic effect against Fusarium oxysporum f. sp. cubense Tropical Race 4 - Yu, Rou Ch’ng; Seok, Christina Yien Yong; Othman, Siti Norhidayah; Mohd Zainudin, Nur Ain Izzati; Mustafa, Muskhazli (Universiti Putra Malaysia Press, 2022)
Bananas are one of the world’s most consumed fruits. Developing countries in the Global South depend on bananas for food security and livelihoods. Still, the banana industry also drives a multinational trade worth billions of US dollars. In addition, banana plants also hold cultural and religious significances in many Asian countries. However, banana production faces several challenges, and one of the major issues is the Fusarium wilt disease caused by the fungus Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4). This disease threatens numerous banana cultivars, including the Cavendish, the most traded banana cultivar. Therefore, the objective of this study was to find effective measures to control the spread of this disease through antagonistic soil bacteria. This study isolated 14 fluorescent, siderophore-producing bacteria with in vitro inhibition rates of 21.73- 50.38% against Foc TR4 from the soil surrounding banana plants. Most of the isolates were identified as Pseudomonas spp. via 16S rRNA sequencing, and phylogenetic analysis based on 16s rRNA sequences showed clustering of isolates congruent with the results of similarity searches. Three isolates that exhibited relatively higher antagonistic activity against Fusarium oxysporum f. sp. cubense compared to other isolates were JBAA132 (50.38%), K2B131 (46.28%), and KTP231 (45.38%). Isolate JBAA132 displayed differences in biochemical characteristics compared to its closest match (Pseudomonas aeruginosa type strain DSM50071). It also demonstrated nitrogen-fixing and phosphate solubilising properties common to plant growth promoters. Therefore, isolate JBAA132 may be further explored as a potential biocontrol agent in curbing the spread of Foc TR4.